2023
DOI: 10.1186/s12889-023-16104-w
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a health education intervention to reduce anxiety in quarantined COVID-19 patients: a randomized controlled trial

Imen Zemni,
Amel Gara,
Hadhba Nasraoui
et al.

Abstract: Introduction The COVID-19 pandemic is regarded as a serious public health concern that boosts levels of stress and anxiety which could be explained by several reasons, including social isolation. In this regard, we aimed to assess the impact of health education on the anxiety level of COVID-19 patients during the isolation period. Methods This is a randomized controlled trial conducted between February 2021 and June 2021. Patients tested positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Several studies have observed associations between prepregnancy lifestyle and maternal and infant health outcomes 11–14 . Recent evidence also suggests that women's nutritional status prior to pregnancy is associated with maternal and infant outcomes 15–20 …”
Section: Before Pregnancymentioning
confidence: 99%
“…Several studies have observed associations between prepregnancy lifestyle and maternal and infant health outcomes 11–14 . Recent evidence also suggests that women's nutritional status prior to pregnancy is associated with maternal and infant outcomes 15–20 …”
Section: Before Pregnancymentioning
confidence: 99%